Female Sexual Function at Three Months Post-delivery in Spontaneous Labor and Cesarean Section - Suntoro, Suntoro; Kayika, I Putu G (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To study the comparison of encouragement, stimuli, orgasm, pain and satisfaction of female sexual function at 3 months postpartum between spontaneous delivery and cesarean section in Dr. Cipto Mangunkusumo Hospital in Jakarta. Method: This was an observational research, sexual function was measured at three months post-delivery with Female Sexual Function Index (FSFI) questionnaire. The study design used was cross sectional with consecutive sampling. Analysis for comparative nonpaired categorical variables was done using Chi square or Fisher analysis. Analysis for confounding variables was carried out using multivariate logistic regression. Result: From 150 respondents, 43.3% had sexual dysfunction, with 52% of the spontaneous labor group and 34% of the cesarean section group. Bivariate analysis showed that occurrence of sexual dysfunction at three months post-spontaneous labor was 1.5 times higher (95% CI 1.02-3.19) compared with cesarean section. Sexual encouragement shows a two-fold difference (95% CI 1.17-3.40) compared to cesarean section. However, orgasm disturbance was 8 times higher (95% CI 1.90-3.58) in the spontaneous labor group, with confounding variable of perineal rupture. Disturbance of sexual stimuli, satisfaction, and pain were not significantly different between spontaneous labor and cesarean section. Multivariate analysis found that spontaneous labor was statistically significant for sexual dysfunction at three months post-delivery in patients with sexual encouragement (RR=2.716, p=0.008) and orgasm accession dysfunction (RR= 6.952, p=0.031). However, the more than 30 years old of age variable was statistically significant in sexual dysfunction variable with RR= 2.60 and p=0.021. Conclusion: Spontaneous labor is statistically significant for sexual dysfunction at three months post-delivery, especially for sexual encouragement and orgasm accession. Meanwhile, the variables with the age of 30 years old or older of age were influential on sexual dysfunction, especially to the sexual stimuli variable. Keywords: labor method, sexual dysfunction, three months postdelivery